CLINICO-BIOCHEMICAL CHARACTERISTIC OF OSTEOARTHROSIS IN ADOLESCENTS - Lebets, I.S .; Kostyurina, N.O.; Matvienko, O.V.; Letyago, G.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In most of adolescents osteoarthrosis develops against the background of systemic  dysplasia of connective tissue and hypermobility of joints and is characterized by scantiness of symptoms in its clinical manifestation which are mainly arthralgias, meteopathy and crunching sounds in the joints. The development of destructive processes in connective tissue structures in the disease is indicated by significant disorders in proteoglycane and collagen metabolism, stimulated by activation of lisosomal ferments. Pathologically destructive process in girls is more pronounced than in boys.